Repairing and Retrofitting of Earthquake-Affected Exterior Beam-Column Connection by Using Resin Concrete - Rifqi Anra Wijaya; Ashar Saputra (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2016)
Reinforced concrete structures may suffer a failure that caused by natural events such as earthquake. If the damaged building still can be used, then a repair (retrofitting) on the damaged section is highly necessary. Retrofitting materials that can be used is the polymer concrete. The purpose of this study was to determine the behavior of beam-column connections after repair (retrofitting) using polymer concrete. Test sample in the form of exterior beam-column connection with cross-sectional size of the column 30 x 30 cm, length of 3.5 m and the size of the beam cross-section of 17 x 30 cm, length 1.8 m, consists of 3 pieces. Experiment test method was based on ACI T1.1-01. All samples were tested in two stages, the first stage of the test until targeted damaged level which controlled by crack width of 0.4 mm. Furthermore, the test object repaired using normal concrete (BKN- 1N) and polymer concrete (BKN-2R and BKN-3R). The second phase of test is done to collapse. Lateral force, deflection, and strain and crack pattern are observed. The data were processed to obtain the load-deflection relationship curve, stiffness, ductility ratio, energy dissipation and model of collapse. Beam-column joint behavior is compared with the acceptance criteria (ACI T1.1-01) to determine whether in accordance with the criteria required. Test results showed the value of the maximum lateral load test object BKN-1N, BKN-2R and BKN-3R,consecutively were 39.2 kN; 43.77 kN and 46.24 kN in the direction of curvature response (+) and the direction of curvature response (-), respectively for 59.1 kN; 62.73 kN and 69.91 kN. BKN-2R test objects have a greater ductility factor of 24.1% in the direction of curvature response (+) when compared with the test object BKN-1N. At the direction of curvature response (-), BKN-2R sample has a greater ductility 39.3% of the sample BKN-1N. Based on ACI T1.1-01, all samples have the response modification factor of 8. From SAP2000 modeling, BKN-1N, BKN-2R, and BKN-3R consecutively showed ability to withstand earthquake forces 3.36 times greater; 3.77 times; and 3.97 times greater than the earthquake forces are designed based on SNI 1726:2012. An advantage of using a resin concrete repair materials is very fast drying time.